2017
DOI: 10.2147/ijn.s138624
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots in imaging, drug delivery and sensor applications

Abstract: Quantum dots (QDs), also known as nanoscale semiconductor crystals, are nanoparticles with unique optical and electronic properties such as bright and intensive fluorescence. Since most conventional organic label dyes do not offer the near-infrared (>650 nm) emission possibility, QDs, with their tunable optical properties, have gained a lot of interest. They possess characteristics such as good chemical and photo-stability, high quantum yield and size-tunable light emission. Different types of QDs can be excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
231
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 507 publications
(252 citation statements)
references
References 58 publications
0
231
0
3
Order By: Relevance
“…Magnetic nanoparticles are easily and scalably manufactured, and they can be detected by MRI for tracking or diagnostic purposes as well as moved toward target cells using a magnetic field . Quantum dots (QDs) are an interesting option as a delivery vehicle with optical properties, as they are designed to be bright, photostable imaging agents and are normally of small size amenable to in vivo trafficking and cellular uptake . As with other inorganic nanoparticles mentioned here, many of these are generally used in combination with other gene delivery materials, such as coatings of PEI, PEG, and other polymers to allow binding and other capabilities required for gene delivery.…”
Section: Nanomaterials For Combinatorial Nucleic Acid Deliverymentioning
confidence: 99%
“…Magnetic nanoparticles are easily and scalably manufactured, and they can be detected by MRI for tracking or diagnostic purposes as well as moved toward target cells using a magnetic field . Quantum dots (QDs) are an interesting option as a delivery vehicle with optical properties, as they are designed to be bright, photostable imaging agents and are normally of small size amenable to in vivo trafficking and cellular uptake . As with other inorganic nanoparticles mentioned here, many of these are generally used in combination with other gene delivery materials, such as coatings of PEI, PEG, and other polymers to allow binding and other capabilities required for gene delivery.…”
Section: Nanomaterials For Combinatorial Nucleic Acid Deliverymentioning
confidence: 99%
“…Highest power conversion efficiency of CdTe solar cells is reported to be as high as ∼20‐22 %, which is probably the highest among all QD based light harvesting devices . Apart from the device applications, in biology and biomedical fields QDs have shown great potential in numerous applications like imaging, sensing, therapy, drug delivery and so on . Exploitation of the CdTe QD fluorescence in biology is extensive for supramolecular interaction study.…”
Section: Introductionmentioning
confidence: 99%
“…The nano-sized semiconductor crystals commonly known as quantum dots (QDs) with their exceptional electronic and optical properties are highly appreciated. 93,94 Specifically intensive fluorescence, high quantum yield, size-tunable light emission, appreciable chemical and photo-stability have revolutionized the concept of nano-based sensing or diagnostics. General elemental composition of QDs includes cadmium (Cd), lead (Pb), mercury (Hg) and zinc (Zn).…”
Section: Quantum Dotsmentioning
confidence: 99%
“…But recently developed ternary I-III-VI QDs contain elements in different form, here "I" represents cupper (Cu) or silver (Ag), "III" represents gadolinium (Ga) or indium (In) and "VI" represents sulfur (S) or selenium (Se). 94 Owing to their extremely small size ranging from 2 to 10 nm QDs are well appreciated and used in biomedical sector as they could conveniently cross the BBB in conjugation with a therapeutic molecule. 94,95 Mahajan et al showed that fluorescent quantum rods (QRs) a form of QD in conjugation with transferring, a targeting molecule and HAAT (Highly Active Antiretroviral Therapy) drug Sequinavir could freely cross an in vitro model of BBB.…”
Section: Quantum Dotsmentioning
confidence: 99%